Environmental liability and redevelopment of old industrial land - Hilary Sigman (Rutgers University, Department of Economics, 2006)
Many communities are concerned about the reuse of potentially contaminated land (brownfields) and believe that environmental liability is a hindrance to redevelopment. However, with land price adjustments, liability might not impede the reuse of this land. Existing literature has found price reductions in response to liability, but few studies have looked for an effect on vacancies. This paper studies variations in state liability rules
Keywords: K32; 330; - specifically; strict liability and joint and several liability; Bodennutzung; Bodensanierung; Kosten; Kosten-Nutzen-Analyse; USA